Bioeconomy as Innovative Component of the Environmental Management - BRYCHKO, Alina; LUKASH, Svitlana; MASLAK, Nataliia; KOVALOVA, Olha (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
The purpose of this article is to identify in Ukraine promising directions of the innovative component of bioeconomy that will contribute to the development of the environmental management. The commonly used definitions of the term bioeconomy are described, the main directions of bioeconomy are considered. It is determined that the main problem of bioeconomy development is its identification with biotechnology. The main problems which are solved with the help of innovative bioeconomy are investigated. The main factors determining the activation of bioeconomy development and a variety of innovative biotechnologies, which contributes to the development of the environmental management, as well as key factors of bioeconomy development, are substantiated. The main recommendations for forming the bioeconomic environment in Ukraine and the prospects for the development of the innovative component of bioeconomy on the domestic market are outlined.